Importance of Economics in Uzbekistan (Eurasian Journal of History, Geography and Economics, 2022)
Economics looks at how governments, businesses, societies, households and individual people make decisions about how, when and where to best use their natural resources. Economics involves many theoretical and conceptual models to study behavior and predict how entities will respond to given changes in market conditions and fiscal policies, among other factors. Economists engage in statistical analysis to study these changes and build predictive and useful economic behavioral models.